Usabilidade das bases de dados nas universidades federais:o caso da UFSM – campus Frederico Westphalen - Santos, Sirlene Aparecida dos (2016)
This study aimed to investigate the use of databases offered by the Federal University of Santa Maria (UFSM), Campus Frederico Westphalen, as well as the difficulties encountered by users. Research subjects were Professors and undergraduate students. The methodology used was quantitative with the gathering of some qualitative data. The developed research was descriptive. The study verified, usin g descriptive statistics, users degree of difficulty in relation to the knowledge and the use of databases. Results indicated that Capes Journals Database and My Library were the databases that got the best reviews and had less difficulties. Regarding the UFSM Journals database, most students stayed neutral on the issues, and finally, the evaluation of the Bank of Theses and Dissertations and the E volution database, the majority of respondents claimed not to use these bases. Most teachers said it is someti mes difficult to search the databases and that the dissemination of such bases is not adequate, which makes it difficult to research on them. This research found that teachers use the UFSM Databases, but what is missing from them is incentive for students to use more these bases to do their academic work. There was the need for greater dissemination and promotion of training courses for those users. In the analysis of qualitative data, this finding was confirmed given that users suggested an improve in the dissemination of these databases, promotion of training for its use and production of materials for guidance, in academia, of this important source of information.